1983
DOI: 10.1084/jem.158.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Helper signals in the plaque-forming cell response to protein-bound haptens.

Abstract: We have been interested in determining the mechanisms by which helper T cells collaborate with B cells in the generation of specific antibody responses. Based on a variety of experimental approaches we have proposed that the induction of B cell IgM plaque-forming cells (PFC) ~ responses to protein-bound haptens requires two types of helper T cell signals, the first both antigen specific and B cell Ia restricted and the second mediated by nonspecific factors, i.e. interleukins (1-6). Studies designed to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
2

Year Published

1984
1984
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
4
19
2
Order By: Relevance
“…These results indicate that Thl cells do not produce the factors necessary for activating resting B lymphocytes, and that neither IL-2 nor IFN -'Y is obligatory for such responses. Such a conclusion contradicts a number of earlier studies showing that IL-2 and IFN-y are important helper factors for B cells (9)(10)(11)(12) . Many of these earlier studies used erythrocytes as antigens (9,12), and it is possible that this represents a unique situation that cannot be extrapolated to soluble proteins .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…These results indicate that Thl cells do not produce the factors necessary for activating resting B lymphocytes, and that neither IL-2 nor IFN -'Y is obligatory for such responses. Such a conclusion contradicts a number of earlier studies showing that IL-2 and IFN-y are important helper factors for B cells (9)(10)(11)(12) . Many of these earlier studies used erythrocytes as antigens (9,12), and it is possible that this represents a unique situation that cannot be extrapolated to soluble proteins .…”
Section: Discussioncontrasting
confidence: 76%
“…Such a conclusion contradicts a number of earlier studies showing that IL-2 and IFN-y are important helper factors for B cells (9)(10)(11)(12) . Many of these earlier studies used erythrocytes as antigens (9,12), and it is possible that this represents a unique situation that cannot be extrapolated to soluble proteins . Moreover, we and others have shown that Thl cells (and their secreted mediators) can help previously activated B cells (23) lated polyclonally in the presence of high concentrations of antigen (4), particularly if the inhibitory effect of IFN-y is neutralized.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Both are released by Thi cells stimulated with antigen-pulsed APC or mitogens (Mosmann et al 1986b). IL-2 can be both a growth and differentiation factor for activated B cells (Liebson et al 1981, Parker 1982, Marrack et al 1982, Brooks & Vitetta 1986) and y-l¥'H has both inhibitory and stimulatory activity on B cells {Roehm et al 1983, OUveret al 1987).…”
Section: Other Lymphokines Involved In the Activation Of B Cellsmentioning
confidence: 99%
“…activity (Tl-class I) or by their poiyvalency and ability to crosslink antigen receptors (Tl-class 2) (Snow et al 1983a(Snow et al , 1983b. On the other hand, most antigens are so-called "T dependent" (TD) (e.g., Trinitrophenol-Keyhole limpet hemocyanin) and require both Signal 1 and Signal 2 to induce B cell activation (Roehm et al 1983). Signal 2 consists of a direct antigen-specific, larestricted T cell-B cell interaction (Singer et al 1982).…”
Section: B Cell Activation Proliferation and Differentiationmentioning
confidence: 99%